Is Apolipoprotein-E modulated in peripheral blood mononuclear cells by IFN-β and is this to related patient responsiveness in multiple sclerosis - O'Toole, Daniel (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2001)
Multiple Sclerosis is a neurodegenerative disorder involving the attack of blood resident T-lymphocytes on the myelin sheath surrounding the neuron. This condition is particularly prevalent amongst white, northern European populations and appears to have both a genetic and environmental aspect to its incidence. Multiple Sclerosis commonly occurs in the Relapsing-Remitting manner, where periods of inflammatory attack are broken by longer phases of partial recovery. IFN-β has been shown to ameliorate attacks and improve recovery during remission. A polipoprotein E is a protein found as part of the lipoprotein particles VLDL, HDL and chylom icron, where it binds to the ApoB/E receptor to deliver cholesterol and free fatty acids. These are much required by the regenerating neuron and the supportive oligodendrocyte to repair cell membranes and myelin sheaths. Physiological Apo-E is produced mainly in the liver, but both the brain resident astrocyte and the infiltrating macrophage also produce significant am ounts. Control of its production is known to occur at transcriptional and post-transcriptional levels. Mutant Apo-E genotypes have been implicated in aberrant repair o f damaged neurons in Alzheimer's disease and acute spinal injury. We have found that, in both the I321N1 human and C6 rat astrocytoma cell lines studied, Apo-E mRNA transcription is inhibited by the inflammatory cytokines TNF-α and IL-1α , but not by IFN-γ. Unfortunately, no cellular or secreted Apo-E protein was detected from these cell lines. In both human primary monocytes and the monocyte cell line THP-1, Apo-E mRNA was inhibited by IFN-γ, and both translated and secreted Apo-E protein was inhibited. TNF-α, IL-1α and TGF-β stimulated Apo-E mRNA transcription, but did not affect cellular or secreted levles. IFN-β failed to alleviate the inhibition o f Apo-E protein in these cells, and instead inhibited it in a similar manner to IFN-γ. No association was found between the Apo- E genotype and the production of Apo-E by primary monocytes.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin